The compliance of the Romanian listed companies with the principles and provisions of the corporate governance code - Bogdana, Oana (Array, 2020)
Starting from the research assumption that the Corporate Governance Code issued by Bucharest Stock Exchange (BSE) aims at building an internationally attractive capital market in Romania, based on best practices, transparency and trust that encourages companies to build a strong relationship with their shareholders and other stakeholders, communicate effectively and transparently and show openness towards all potential investors, in this paper we would like to present the degree of compliance of the companies listed on the Bucharest Stock Exchange with the principles and provisions of the Corporate Governance Code. The aim of this paper is achieved by presenting and commenting on the principles issued by the BSE regarding the corporate governance and by analysing the Corporate Governance Reports of the companies, presenting at the same time the compliance of the listed companies with these principles and provisions, by using the data issued in 2018 by the entities included in our study, namely the listed companies on the main market of the Bucharest Stock Exchange. Our analysis reflects that, although the provisions and principles of the Corporate Governance Code are not mandatory for the listed companies, they are largely implemented in the activity of companies because an efficient corporate governance system can represent a competitive advantage for any economic entity in the context of globalisation.